Real-time simulation of liquid process plant using GENESIS software - Aldebrez, F.M.; Mohamed , M.B.; Sulaiman, S (1997)
Presents the development of a mathematical model of a multivariable liquid process plant. This multivariable liquid process rig incorporates two interacting loops; level control loop and temperature control loop. Based on the developed model, an experiment was conducted on the actual system for the purpose of real-time data collection and estimating the parameters of the model using a real-time software called GENESIS. This software is a real-time, multitasking software used in this work for running the actual plant and collecting the real data from the actual process. It is also used to perform a computer simulation study on the developed model to verify its performance. The simulation study was performed in terms of three case studies, that are, level control loop, temperature control loop and interaction loop respectively. The performance of each loop was investigated and the extent of the interaction effect between the two single loops was also highlighted